Implicature In Courageous Movie Script - Lasriani Sitanggang; Neil Amstrong (ELITE: Journal of English Language and Literature, 2020)
This research aimed to describe the Implicature in Courageous Movie script by Alex Hendrick. This research focused on how is implicature used in Courageous Movie Script by Alex Hendrick. The findings revealed that the implicature used in the object were two that were conventional implicature and conversational implicature. The result is conventional implicature found is 3 data and conversational implicature is 17 data. Conventional Implicature is found in many Nathan Hayes conversations that discuss how God's love is. Many implicatures are found in their conversation. There were many hidden meanings that lead to misunderstanding because of the hidden meaning spoken by their father. The children in this movie did not understand the meaning of their father who did not want them to do what they want. They thought their father did not love them. In this case, the children do not understand the context and make a misunderstanding. The researcher also did a test for implicature. The researcher also did a test for implicature. Based on the test for whole data, the implicature containing cancellability is 1 data, the implicature containing non-detachability 17 data, the implicature containing the calculability 17 data, and the implicature containing non-conventionality is 17 data. There are 17 data that contain non-detachability, calculability, and nonconventionality, and only 1 data that contains cancellability, non-detachability, calculability, and non-conventionality. It can be concluded that the test for implicature is most often found only three and one other is rarely found although it still exists.